Putting Jesus in his place : the case for the deity of Christ - Bowman, Robert M.; Komoszewski, J. Ed. (Grand Rapids, MI : Kregel Publications, 2007)
"Putting Jesus in His place" demonstrates that the New Testament--from beginning to end--clearly reveals Jesus' divine identity. What's more, it shows that belief in Jesus as God was the conviction of his original Jewish followers, rooted in Old Testament theology and in what Jesus himself said and did.
The devotion revolution : Jesus shares the honors due to God -- All glory, laud, and honor -- The worship of the Carpenter -- What a friend we have in Jesus -- Sing to the Lord -- The ultimate reverence package -- Like Father, like Son : Jesus shares the attributes of God -- Beyond resemblance -- Jesus existed before He was born! -- Jesus has always been there -- Jesus : the right stuff -- He's got what it takes -- Name above all names : Jesus shares the names of God -- Name one -- Immanuel : God with us -- He is Lord -- Jesus is it from A to Z -- Infinitely qualified : Jesus shares in the deeds that God does -- Meet your Maker -- He's got the whole world in His hands -- The Way, the Truth, and the Life -- Here comes the judge -- The best seat in the house : Jesus shares the seat of God's throne -- Jesus takes the stand -- God's right-hand man -- Jesus takes His seat -- Conclusion : the case for the deity of Christ.
Includes bibliographical references (p. 289-366) and index.
Keywords: Jesus Christ -- Divinity